Arah Pengembangan Ekosistem Halal dalam Kebijakan Publik: Studi Hukum Islam dan Peraturan Perundang-Undangan di Indonesia - Marnita, Marnita (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This research aims to explore the direction of halal ecosystem development in public policy in Indonesia. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that implementing the halal ecosystem concept in public policy in Indonesia has had significant social and economic impacts. Legislation such as Law Number 33 of 2014 has supported establishing and developing infrastructure and the halal product certification process. Additionally, an increase in the Islamic economic literacy index indicates a growth in public awareness. In contrast, a decline in the Sharia financial inclusion index identifies challenges that must be addressed. Therefore, it is recommended that the Government continue to update and adjust legislation that supports the halal economy, ensuring that these policies are responsive to global dynamics and domestic needs. Businesses need to enhance innovation and standardize products to maintain trust and meet consumers’ evolving expectations. Educational institutions should continue to expand research and education programs that support disseminating knowledge on Islamic economics and halal practices, particularly in addressing the challenges of literacy and financial inclusion in Sharia. Finally, Religious Leaders are expected to play an active role in educating the public, guiding the community with accurate knowledge about Islamic law, and ensuring that halal practices are effectively integrated into daily life. Synergy and integrated collaboration among all parties will strengthen Indonesia’s halal ecosystem, foster innovation, and maintain the country’s position as a leader in the global halal market.